Orthogonal Polynomials - 18.35 Pollaczek Polynomials

From testwiki
Revision as of 17:26, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
18.35.E4 ( λ - i τ a , b ( θ ) ) n n ! e i n θ F 1 2 ( - n , λ + i τ a , b ( θ ) - n - λ + 1 + i τ a , b ( θ ) ; e - 2 i θ ) = = 0 n ( λ + i τ a , b ( θ ) ) ! ( λ - i τ a , b ( θ ) ) n - ( n - ) ! e i ( n - 2 ) θ Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 𝜃 Gauss-hypergeometric-F-as-2F1 𝑛 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝜆 1 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 superscript 𝑒 2 imaginary-unit 𝜃 superscript subscript 0 𝑛 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 2 𝜃 {\displaystyle{\displaystyle\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(\theta)% \right)_{n}}}{n!}e^{\mathrm{i}n\theta}\*{{}_{2}F_{1}}\left({-n,\lambda+\mathrm% {i}\tau_{a,b}(\theta)\atop-n-\lambda+1+\mathrm{i}\tau_{a,b}(\theta)};e^{-2% \mathrm{i}\theta}\right)=\sum_{\ell=0}^{n}\frac{{\left(\lambda+\mathrm{i}\tau_% {a,b}(\theta)\right)_{\ell}}}{\ell!}\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(% \theta)\right)_{n-\ell}}}{(n-\ell)!}e^{\mathrm{i}(n-2\ell)\theta}}}
\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n}}{n!}e^{\iunit n\theta}\*\genhyperF{2}{1}@@{-n,\lambda+\iunit\tau_{a,b}(\theta)}{-n-\lambda+1+\iunit\tau_{a,b}(\theta)}{e^{-2\iunit\theta}} = \sum_{\ell=0}^{n}\frac{\Pochhammersym{\lambda+\iunit\tau_{a,b}(\theta)}{\ell}}{\ell!}\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n-\ell}}{(n-\ell)!}e^{\iunit(n-2\ell)\theta}
0 < θ , θ < π formulae-sequence 0 𝜃 𝜃 𝜋 {\displaystyle{\displaystyle 0<\theta,\theta<\pi}}
(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n))/(factorial(n))*exp(I*n*theta)* hypergeom([- n , lambda + I*((a*cos(theta)+ b)/(sin(theta)))], [- n - lambda + 1 + I*((a*cos(theta)+ b)/(sin(theta)))], exp(- 2*I*theta)) = sum((pochhammer(lambda + I*((a*cos(theta)+ b)/(sin(theta))), ell))/(factorial(ell))*(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n - ell))/(factorial(n - ell))*exp(I*(n - 2*ell)*theta), ell = 0..n)
Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n],(n)!]*Exp[I*n*\[Theta]]* HypergeometricPFQ[{- n , \[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, {- n - \[Lambda]+ 1 + I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, Exp[- 2*I*\[Theta]]] == Sum[Divide[Pochhammer[\[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), \[ScriptL]],(\[ScriptL])!]*Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n - \[ScriptL]],(n - \[ScriptL])!]*Exp[I*(n - 2*\[ScriptL])*\[Theta]], {\[ScriptL], 0, n}, GenerateConditions->None]
Error Successful - Successful [Tested: 300]
18.35.E6 w ( λ ) ( cos θ ; a , b ) = π - 1 2 2 λ - 1 e ( 2 θ - π ) τ a , b ( θ ) ( sin θ ) 2 λ - 1 | Γ ( λ + i τ a , b ( θ ) ) | 2 superscript 𝑤 𝜆 𝜃 𝑎 𝑏 superscript 𝜋 1 superscript 2 2 𝜆 1 superscript 𝑒 2 𝜃 𝜋 subscript 𝜏 𝑎 𝑏 𝜃 superscript 𝜃 2 𝜆 1 Euler-Gamma 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 2 {\displaystyle{\displaystyle w^{(\lambda)}(\cos\theta;a,b)=\pi^{-1}\*2^{2% \lambda-1}\*e^{(2\theta-\pi)\*\tau_{a,b}(\theta)}\*(\sin\theta)^{2\lambda-1}\*% {\left|\Gamma\left(\lambda+\mathrm{i}\tau_{a,b}(\theta)\right)\right|^{2}}}}
w^{(\lambda)}(\cos@@{\theta};a,b) = \pi^{-1}\*2^{2\lambda-1}\*e^{(2\theta-\pi)\*\tau_{a,b}(\theta)}\*(\sin@@{\theta})^{2\lambda-1}\*\abs{\EulerGamma@{\lambda+\iunit\tau_{a,b}(\theta)}}^{2}
a b , b - a , λ > - 1 2 , 0 < θ , θ < π formulae-sequence 𝑎 𝑏 formulae-sequence 𝑏 𝑎 formulae-sequence 𝜆 1 2 formulae-sequence 0 𝜃 𝜃 𝜋 {\displaystyle{\displaystyle a\geq b,b\geq-a,\lambda>-\frac{1}{2},0<\theta,% \theta<\pi}}
(w(cos(theta); a , b))^(lambda) = (Pi)^(- 1)* (2)^(2*lambda - 1)* exp((2*theta - Pi)*((a*cos(theta)+ b)/(sin(theta))))*(sin(theta))^(2*lambda - 1)* (abs(GAMMA(lambda + I*((a*cos(theta)+ b)/(sin(theta))))))^(2)
(w[Cos[\[Theta]]; a , b])^(\[Lambda]) == (Pi)^(- 1)* (2)^(2*\[Lambda]- 1)* Exp[(2*\[Theta]- Pi)*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])]*(Sin[\[Theta]])^(2*\[Lambda]- 1)* (Abs[Gamma[\[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])]])^(2)
Translation Error Translation Error - -